Comparing the Preventive Effect of Combination of Ketamine with Metoclopramide or Fentanyl on the Postoperative Pain after Laparoscopic Cholecystectomy under General Anesthesia - Seyed Mortaza Heidari-Tabaee-Zavare; Mehran Qanavi; Leila Raeesi (مجله دانشکده پزشکی اصفهان, 2015)
Background: Pain is one of the most common postoperative complications that can be reduced via different methods like combination of two or more drugs to make synergistic effect. This research aimed to comparing the preventive effect of using combination of ketamine and fentanyl or ketamine and metoclopramide on the postoperative pain after laparoscopic cholecystectomy.